Merancang Media Edukasi Digital: Pendekatan Design Thinking dalam Pengembangan E-Booklet Ekowisata Mangrove - Ilma Mufida Inayati; Sunarto Sunarto; Ahmad Prawira Dhahiyat; Donny Juliandri Prihadi; Shafira Bilqis Annida (Yayasan Literasi Sains Indonesia, 2025)
This study aims to design an ecotourism e-booklet on mangrove conservation for visitors of Angke Kapuk Nature Tourism Park (TWA Angke Kapuk) using a design thinking approach. The background of this research is the limited availability of interactive educational media in the park, which causes tourists to focus mainly on recreation without gaining a deeper understanding of mangrove conservation. A mixed methods approach was applied, combining surveys with 30 visitors, interviews with park managers, and design thinking stages including empathize, define, ideate, prototype, and test. Initial surveys revealed a low satisfaction level with existing media (average score 2.93), while interest in a digital e-booklet was very high (86.7%). The developed prototype contains information about mangrove ecosystem functions, seedling processes, planting techniques, monitoring activities, and includes interactive quizzes as well as QR codes linking to videos. Testing results indicated a significant increase in visitor satisfaction (average 4.36) and conservation awareness, with respondents stating that the e-booklet provided new knowledge (mean 4.50) and raised awareness of the importance of protecting mangroves (mean 4.63). Thus, the e-booklet is proven effective as an interactive educational medium that supports conservation efforts and sustainable ecotourism development in TWA Angke Kapuk.